Application of Nor Sand Constitutive Model in a Highway Fill Embankment Slope Stability Failure Study - Jiliang Li; Thiago Fernandes Leao (Salehan Institute of Higher Education, 2018)
This paper presents a case study of a static load induced liquefaction in a simple roadway widening project constructed in north eastern part of Ohio in 2008. The widening required an embankment fill, which moved nearly 4 feet vertically and 1 foot laterally after two days of installation. The main objective of the work is to demonstrate how a simple Constitutive model, in this case Nor Sand model, can represent the static liquefaction in loose sand layers under specific conditions. A set of parameters is assumed based on the soil properties and an Excel Spreadsheet is used for simulations of triaxial compression of sand. It was considered that the situation which led to the failure, and the situation after the solution adopted. Moreover, slope stability analysis is provided for validation of the original results using a commercial software. It was found that the model can represent through stress strain curves and stress paths the behavior of the soil layer which led to the embankment fill movement. As the original work considered only slope stability analysis to explain this phenomenon, the present study shows a different approach for the case study, and this is the main contribution of this research.